Smartphone Fundus Videography For Documentation Of Retinal And Optic Nerve Head Diseases - Rajesh Hans; Mohmad Uzair; Aditi Kaushik (Delhi Journal of Ophthalmology)
Ophthalmological services are required everywhere throughout the country. The lack of availability of the equipment's like fundus camera at most of the smaller centers is still a discouraging factor for documentation of retinal and optic nerve head diseases. The smaller centers fulfill this need by referring the patients to tertiary or higher centers. Here, we describe a technique of Smartphone Fundus videography (SFV), which may prove useful for the necessary documentation. The generated data by this technique may be stored in any easily available electronic hardware and software. This data may also be used for temporal comparison of the diseases in the patients following up at various clinics by easily sharing the data using widely available smartphone applications.